SEMANTIC STRUCTURE OF PHRASEOLOGICAL UNİTS IN MODERN ENGLISH - Rakhmatullayeva Makhbuba Zafar kizi (American Journals Publishing, 2023)
The aim of the work is to cover the issues of researching the semantics and structure of phraseological units. An analysis of the characteristics of phraseological semantics is one of the problems causing numerous scientific disputes.
Keywords: phraseological units, aphorisms, cosmic technique, forming interjections, idioms